Hypertension treatment in the oldest-old: focus group interviews with Swedish general practitioners - Marjo Berkhout; Kristina Bengtsson Boström; Anna-Lena Östberg (Taylor & Francis Group, 2022)
AbstractObjective This study explored the considerations and experiences of Swedish General Practitioners (GPs) of hypertension treatment in patients 80 years and above.Design Qualitative design with focus group interviews. Data were analysed by qualitative content analysis.Setting Primary health care centres (PHCCs), both rural and urban, in the Region of Västra Götaland, Sweden.Subjects GPs and GP trainees working at PHCCs in 2019 and 2020. Five focus group interviews with 24 physicians were performed.Main outcome measures Considerations and experiences of hypertension treatment in the oldest-old.Results Eighteen GPs and six GP trainees participated in the study. The latent content was formulated in a theme: 'The physician's decision-making in the treatment of hypertension in the oldest-old implies the inclusion of both medical and humanistic considerations.' The manifest content constituted three main categories: 'The patient characteristics' included medical condition, behavioural factors and daily life. 'The physician's role' described the GP as a professional and her/his experienced support. 'The treatment decision' considered these categories and involved risk-benefit balancing and communication. For the future, the participants proposed better guidelines for the oldest-old multimorbid patients, increased teamwork, continuous cooperation with nurses and better cooperation with hospital physicians.Conclusion Hypertension care for the oldest-old was experienced as complicated by GPs, due to the need of balancing medical and humanistic considerations. The GP's clinical experience and the received support were of importance when making the treatment decision based on risk-benefit balancing and communication with the patient.Key pointsGPs experienced the task of caring for the oldest-old patients with hypertension as complicated.Patient factors like multimorbidity, polypharmacy, behavioural factors and the patient's condition of daily life were identified.Clinical experience and the experienced support at the PHCC were discussed as important for the GPs' treatment decision.Treatment decisions for the oldest-old patients with hypertension were based on risk-benefit balancing and communication with the patients.